GLOBAL DRIVERS SETTING DESERTIFICATION RESEARCH PRIORITIES: INSIGHTS FROM A STAKEHOLDER CONSULTATION FORUM. (14th May 2013) - Bisaro, Alexander; Kirk, Michael; Zdruli, Pandi; Zimmermann, Willi; Fleskens, Luuk; Stringer, Lindsay C.
ABSTRACT Recent rapid changes in global scale drivers of desertification, land degradation and drought (DLDD) have two important consequences for drylands. First, changes in these drivers, for example in food and energy prices, make improving interventions in drylands more urgent because of their potential impacts. Second, these changes introduce new knowledge gaps regarding both the potential impacts on social‐ecological dryland systems and the design of options to take advantage of opportunities. This paper identifies the most salient research needs in DLDD in drylands brought on by global drivers. The question was addressed through an iterative stakeholder consultative forum. First, relevant global scale drivers were identified through a literature review and preliminary consultation. Next, stakeholders and experts were further consulted to identify research priorities given rise to by these drivers. Identified research priorities were as follows: (i) assessing impacts of rising prices on DLDD in mixed market and subsistence production contexts; (ii) assessing options and limits of agricultural modernisation on fragile lands; (iii) developing methods for assessing land‐use trade‐offs and mapping productive lands; (iv) modelling and participatory methods for monitoring and evaluating soil carbon sequestration; (v) developing policy frameworks to regulate impacts of investment on the environment and local livelihoods; (vi) participatory modelling for regional and local adaptation planning; and (vii) valuation of non‐market land degradation outcomes including biodiversity loss. Concluding, we call for a forward‐looking interdisciplinary drylands research agenda with an increased emphasis on governance to address these priorities. Copyright © 2013 John Wiley & Sons, Ltd.